Nutritional status of elderly in rural areas of Haldwani, Nainital district of Uttarakhand - Bartwal, Janki; Rawat, Chandra Mohan S.; Awasthi, Sadhana (International Journal Of Community Medicine And Public Health, 2017)
Background: Diet and nutrition are important factors in the promotion and maintenance of good health throughout the entire life course. Ageing is often accompanied by the occurrence of illness, which may increase the risk of nutritional deficiency. This study was conducted with the objective to know the nutritional status of elderly. Methods:A community based cross-sectional study in rural areas of Haldwani was done over a period of one year. Two stage sampling technique was used to collect the data from 440 elderly aged 60 years and above on a pretested semi structured questionnaire. Data was entered into Microsoft excel sheet, coded and then analysed using SPSS version 16. Chi square test was used as test of significance and p<0.05 was considered significant. Results: Most (59.54%) of the elderly belongs to 60-69 years of age, females (57.5%) outnumbered males. Majority of the aged were married (59.77%), living in joint families (92.5%), illiterate (60%), not working (78.64%) and belonging to class III socio-economic status (59.09%). Overall 51.36% of the elderly were non vegetarian. The difference in dietary habits of male and female elderly was found statistically significant (ᵡ2=21.4, p=0.001). The difference in BMI of elderly males and females were found statistically significant (ᵡ2=10.0, p=0.019). BMI decreases with increase in age and this was found statistically significant (ᵡ2=13.6, p=0.034). Conclusions:Nutritional assessment of the elderly is essential because it is one of the measures to assess the health status of elderly.